Resposta nutricional do porta-enxerto de limoeiro 'citrumelo' à aplicação de nitrogênio, fósforo e potássio - Wyllyam do Vale, Diego [UNESP]; de Mello Prado, Renato [UNESP]; Natale, William [UNESP]; Ursulino Alves, Adriana [UNESP] (My University, 2008)
The effect of the application of three doses N, P and K on substrates on the nutritional status of root stock of 'Citrumelo' lemon (Citrus paradisi x Poncirus trifoliata) was evaluated. The experiment followed a fully randomized factorial design (3x3) (three nutrients x three doses plus a control) with three replicates. The treatments consisted of D1 = half standard dose, D2 = one standard dose and D3 = twice standard dose, in addition to the control that did not received fertilization at all. At four months after the emergence of the root stock of lemon 'Citrumelo' the plants tissue (leaves) were determined for nutrients analysis to obtain its accumulation. The results showed that plants of lemon 'Citrumelo' 'Swingle' are responsive to the application of N, P and K. The application of nitrogen showed a linear accumulation pattern of N and K, while the applications of phosphorus and potassium provided a quadratic response.
Nutriotional response of rootstock of lemon 'citrumelo' to nitrogen, phosphorus and potassium aplication
Keywords: Citrus paradisi; Fertilizer; Nitrgênio; Nutrition of plants; Phosphorus; Poncirus trifoliata; Potassium